Jewish Meditation in Counseling. Issue 2 (11th October 2020) - Hilert, Alexander J.; Gutierrez, Daniel
Abstract : Many counselors integrate meditation into treatment with clients. Although meditation can be presented as a secular practice, it also holds spiritual and religious relevance for many faith communities. In this article, we explore the use of Jewish meditation as a spiritually oriented treatment intervention with Jewish clients. Literature examining the relationships among counseling, the Jewish population, and Jewish meditation is presented. This article also includes practical considerations for integrating Jewish meditation into counseling.